2017
DOI: 10.1136/archdischild-2016-312018
|View full text |Cite
|
Sign up to set email alerts
|

Deformational plagiocephaly in normal infants: a systematic review of causes and hypotheses

Abstract: The evidence on the aetiology of DP is fragmentary and heterogeneous. In addition, factors possibly relevant to the development of DP have not been appreciated in the scientific discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 33 publications
1
45
1
2
Order By: Relevance
“…In previous studies, a significant neurodevelopmental delay was observed in children with deformational plagiocephaly, although no definitive relationship between the severity of deformation and the degree of developmental delay was found (the psychomotor development index was only affected by congenital anomalies) [41]. On the other hand, a systematic review showed a positive association between plagiocephaly and developmental delay in 13 of 19 studies, including four of five studies with a "strong" methodological quality [27].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In previous studies, a significant neurodevelopmental delay was observed in children with deformational plagiocephaly, although no definitive relationship between the severity of deformation and the degree of developmental delay was found (the psychomotor development index was only affected by congenital anomalies) [41]. On the other hand, a systematic review showed a positive association between plagiocephaly and developmental delay in 13 of 19 studies, including four of five studies with a "strong" methodological quality [27].…”
Section: Discussionmentioning
confidence: 93%
“…The risk factors most frequently reported in the etiology of plagiocephaly are male gender, a supine sleep position, limited neck rotation or preference in head position, being firstborn, a lower level of activity, and a lack of tummy time [41]. Studies reporting the possible etiologies of plagiocephaly have analyzed a wide range of environmental and biological factors but have included few suggestions on the potential influence of everyday baby care environments [41]. The concordance between these studies is very poor for most exposures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Canadian cohort study, an estimated 47% of infants had some degree of NSP at 7–12 weeks of age (Mawji, Vollman, Hatfield, McNeil, & Sauve, ). The most commonly reported risk factors are firstborn, male, limited neck rotation or preference in head position, supine sleep position, lower level of activity and lack of tummy time (De Bock, Braun, & Renz‐Polster, ). The prevalence seems to peak at 4 months and then decreases as infants grow older (Hutchison, Hutchison, Thompson, & Mitchell, ).…”
Section: Introductionmentioning
confidence: 99%
“…Positional head deformity is caused by external pressures on the rapidly developing skull from prolonged exposure to one position. It is reported that the risk factors for positional head deformity included premature delivery, multiple gestation, congenital muscular torticollis, oligohydramnios and other intra‐uterine constraint . With early detection and intervention, most positional head deformities can be treated conservatively with postural correction training or a head orthosis (‘helmet’) .…”
mentioning
confidence: 99%